A Novel Miniaturised Sensor for Combined Static and Dynamic Pressure Measurements in Harsh Environments. (2016) - Zarfl, C.; Schmid, P.; Schmid, U.
Abstract: In this study a sensor for harsh environments is presented, that combines the advantages of two principles for pressure monitoring in one package. Highly dynamic and very precise measurements are performed with piezoelectric single crystals. In addition, the static pressure is monitored with platinum thin film strain gauges, designed for high temperature environments. A novel membrane transmits the environmental pressure to both sets of measuring elements that are placed in a closed housing. Experiments show that the setup is stable at least up to 500̊C. Sensor calibration is performed at room temperature with oil at pressure levels ranging up to 50bar. The linearity of the piezoelectric system is within ±1.2% FSO, the linearity of the strain gauges within 3.5% FSO. For demonstration purposes, an oscillating pressure output gained from both piezoelectric and strain gauge sensor elements is presented at 12Hz, showing a good agreement between both transducer principles.